Evaluating the Development of the Integration if Emerging Economies Under the New İnternational Economy, the BRICS Group as A Model - Munaf Marza Neama (International Journal of Economics, Commerce, and Management, 2025)
The rapid economic and political rise of emerging countries has led to a change in the dynamics of power in the global system, as economic blocs have provided an important developmental role in the international economy. "For example, the BRICS group has occupied an important role as an influential group on the stage of international politics، Accordingly, the aim of the research was within the framework of seeking to know the developmental role of emerging economies in the global economy, in addition to knowing the impact of economic blocs in those countries in contributing to achieving international economic stability, according to the hypothesis that economic blocs in emerging countries have a positive role in developing the global economy. "The research was used The analytical method in verifying the research hypothesis. The research concluded that the BRICS bloc played many roles in global economic performance, which contributed to strengthening the institutional aspect of the BRICS countries, represented by the New Development Bank and the Emergency Reserve Arrangement, which are two of the main features of cooperation between emerging economies and developing countries". Hence, this makes it necessary to understand the role of BRICS as an important platform in the international system.